2014
DOI: 10.1016/j.jalz.2013.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Social cognition in Alzheimer's disease: A separate construct contributing to dependence

Abstract: The extent to which social cognitive changes reflect a discrete constellation of symptoms dissociable from general cognitive changes in Alzheimer’s disease (AD) is unclear. Moreover, whether social cognitive symptoms contribute to disease severity and progression is unknown. The current multicenter study investigated cross-sectional and longitudinal associations between social cognition, general cognition, and dependence in 517 participants with Probable AD. Participants were followed every 6-months for 5.5 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 50 publications
3
43
1
Order By: Relevance
“…ToM in AD 14 on EF in AD, directly contradicting a recent study that highlighted the independence of ToM impairment and general cognition performance in AD (Cosentino et al, 2014).…”
Section: A C C E P T E D Accepted Manuscriptcontrasting
confidence: 77%
See 3 more Smart Citations
“…ToM in AD 14 on EF in AD, directly contradicting a recent study that highlighted the independence of ToM impairment and general cognition performance in AD (Cosentino et al, 2014).…”
Section: A C C E P T E D Accepted Manuscriptcontrasting
confidence: 77%
“…These deficits persist over time and also rapidly worsen in bvFTD patients with marked mPFC atrophy compared to those with limited mPFC atrophy (Kumfor et al, 2014). By contrast, the evidence for ToM impairment in AD has lacked general consensus on whether deficits on ToM tasks are a result of an authentic impairment of ToM (Cosentino et al, 2014;Freedman et al, 2013;Moreau et al, 2016), or due to deteriorating general cognition in the disease, an approach that is compatible with the interactive models of ToM (Dodich et al, 2016;Stone et al, 2006). Few studies in support of a stand-alone ToM deficit in AD have shown that AD patients could fail on basic ToM tasks like gaze-processing (Laisney et al, 2013) and inferring someone's (first-order false) beliefs (Freedman et al, 2013;Le Bouc et al, 2012).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to conduct trials on new therapeutics with enough statistical power to gain approval, thousands of participants need to be enrolled and tracked over many months or even years for prevention trials. Participation in clinical studies can also be challenging for individuals affected by Alzheimer's causing slower enrollment rates and greater drop-out rates (Cerami et al, 2014;Cosentino et al, 2014;Stephens et al, 2014). Many participants also have co-existing conditions that may prevent their participation or may be exclusion criteria for the study.…”
Section: Challenges and Opportunities In Prevention Studiesmentioning
confidence: 99%